UJI EFEKTIVITAS REBUSAN DAUN KAYU JAWA (Lannea coromandelica) SEBAGAI INSEKTISIDA Aedes aegypti: BOILED KAYU JAWA LEAVES (Lannea coromandelica) EFFECTIVENESS AS Aedes aegypti INSECTICIDE - Pradana, Muhammad Sungging; Karimah, Sulis Tiani; Herawati, Dheasy (Jurnal SainHealth, 2024)
Aedes aegypti is a vector of Dengue Hemorrhagic Fever (DHF). DHF is transmitted through the bite of the Aedes aegypti mosquito which carries the virus in its body. Mosquito eradication can use natural insecticides derived from natural agent such as plants metabolites that are toxic to insects. Kayu Jawa leaf (Lannea coromandelica) is a wild plant that is easy to find. Kayu jawa leaves contain secondary metabolites such as saponins, flavonoids, polyphenols and tannins which has insecticide activity. This research was an experimental test using kayu jawa leaves (L. coromandelica) decoction at 20%, 40%, 60% and 100% to eradicate A. aegypti. Test results show that 100 % concentration of L. coromandelica leaves decoction has the greatest activity to eradicate A. aegypti. The lowest activity shown in 20% concentration. This is due to the performance of secondary metabolite compounds from L. coromandelica leaves. The conclusion of this research is L. coromandelica has an activity as an A. aegyti insecticides.